Meteorological and hydrographic service of the army of the Second Polish Republic - Czernielewski, Konrad Aleksander (Armia kontra natura, 2020)
The author of the article discussed the history of the meteorological and hydrographic service of the Polish Army in 1919–1939. At the beginning of his considerations, he presented a brief outline of the development of meteorological and hydrographic observations in Poland from the end of the Middle Ages to the outbreak of World War I. He showed the beginnings of forming state and military meteorological and hydrographics service in 1919. He devoted a lot of attention to the activities of the State Institute of Meteorology – an institution closely cooperating with the Ministry of Military Affairs, the General Staff of the Polish Army and its branches.He also presented the history of the hydrographic services of the Polish Navy. Before 1939, Poland had great achievements in hydrographic research. As early as 1926, she became a member of the International Hydrographic Office based in Monaco. The Navy’s Hydrographic Office was the official representative of Poland in the International Bureau.The author devoted a lot attention to the activities of meteorological services for the Polish aviation – mainly military, but also the cooperation of military meteorologists with Polish artillery and armaments service. He acquainted readers with the issues of training meteorological and hydrographic services in Poland in 1918–1939. He also presented the organizational structure of these services and their commanding staff. He introduced readers to technical issues: he presented the instrumentations, ways and methods for observing natural phenomena and recording them.In final conclusions he presented his assessment of the activities of meteorological and hydrographic services of the Polish Army. He rated them very highly – they were well organized and well equipped with specialist equipment, they cooperated with numerous scientific institutions. They were highly rated in the interwar period by representatives of European armies. This is evidenced by the fact that at the beginning of March 1938 he asked for information about the organization of Polish meteorological and hydrographic services to the Military Attaché of Finland.